The Role of Social Capital on International Trade Transactions at Wini Market, In Realizing Social Harmonization of Indonesia-Timor Leste Border Community - Suwartiningsih, Sri; Purnomo, Daru; Lahade, John R. (International Journal of Criminology and Sociology, 2022)
May 20, 2002, East Timor was internationally recognized as an independent country by the name of Timor Leste with extraordinary support from the United Nations and thus officially became an independent state separate from Indonesia. One of the border areas that were selected as the research site was the Wini border, North Central Timor Regency, East Nusa Tenggara Province. In the Wini region, there is a market called the Wini market. This study aims to explain the role of social capital in international trade transactions in the Wini Market because it involves different citizens from Timor Leste and Indonesia. The research used a descriptive approach and qualitative research method. Theories used are Social Capital theory, Classical Economic theory, and the concept of Cross-Border Trade. The research shows that the people from Timor Leste conduct economic transactions, in this case, shopping at the Wini market every Monday to meet their food, clothing, and other needs. For border communities, the interactions in the Wini market are not only for trade transaction but also to interact with their relatives and others. The results of this study may contribute to the knowledge of the relationship between the science of International Relations and Sociology. From a practical point of view, a border policy can be applied in the economic sector and in the mechanism of mutually beneficial trade transactions between citizens of different countries. The elements of social capital such as trust, norms, and networks have functioned in the process of trade transactions. The application of social capital in international trade economic practices in the Wini Market is what keeps social harmony in the context of international trade transactions in the Wini Market.